Réponses

2014-04-22T11:46:22+02:00
1)a) Cos(π/4)=OH/OM
Donc OH=OM*cos(π/4)
OM=1 et cos(π/4)= \frac{ \sqrt{2}}{2}
Donc OH= \frac{ \sqrt{2}}{2}
I'H=I'O+OH=1+ \frac{ \sqrt{2}}{2} = \frac{2+ \sqrt{2}  }{2}

b) I'M²=I'H²+MH² or
Sin(π/4)=MH/OM donc MH=OM*sin(π/4)= \frac{ \sqrt{2}}{2}
Donc
I'M^{2}=(\frac{2+\sqrt{2}}{2})^{2}+(\frac{\sqrt{2}}{2})^{2}
I'M^{2}=\frac{4+4\sqrt{2}+2}{4}+\frac{2}{4}=\frac{8+4\sqrt{2}}{4}=2+\sqrt{2}
Donc I'M= \sqrt{2+ \sqrt{2}}

2) D'après le théorème de l'angle au centre :
MOI=2*MI'I donc MI'I=π/8
Cos(π/8)=I'H/I'M
Cos(\frac{\pi}{8})= \frac{2+ \sqrt{2} }{2 \sqrt{2+\sqrt{2}}}=\frac{\sqrt{2+\sqrt{2}}}{2}

Sin(π/8)=MH/I'M
Sin(\frac{\pi}{8}= \frac{\sqrt{2}}{2\sqrt{2+\sqrt{2}}}
  • Utilisateur Brainly
2014-04-22T13:18:28+02:00
1)a) Cos(π/4)=OH/OM
Donc OH=OM*cos(π/4)
OM=1 et cos(π/4)=
Donc OH=
I'H=I'O+OH=1+=

b) I'M²=I'H²+MH² or
Sin(π/4)=MH/OM donc MH=OM*sin(π/4)=
Donc


Donc I'M=

2) D'après le théorème de l'angle au centre :
MOI=2*MI'I donc MI'I=π/8
Cos(π/8)=I'H/I'M


Sin(π/8)=MH/I'M